Pengaruh Budaya Organisasi dan Kompensasi Terhadap Loyalitas Karyawan PT Parako Ekatama Rangkasbitung di Era Pandemi COVID-19 - Maesaroh Maesaroh; Eva Indriyani (Universitas La Tansa Mashiro, 2022)
This study aims to analyze the influence of organizational culture on employee loyalty of PT Parako Ekatama Rangkasbitung, the effect of compensation on employee loyalty of PT Parako Ekatama Rangkasbitung, the influence of organizational culture and compensation on employee loyalty of PT Parako Ekatama Rangkasbitung. The purposes of this study were 1) to determine organizational culture on employee loyalty at PT Parako Ekatama Rangkasbitung 2) to determine the effect of compensation on employee loyalty at PT Parako Ekatama Rangkasbitung 3) to determine organizational culture and compensation influence employee loyalty at PT Parako Ekatama Rangkasbitung. The research method used is quantitative method and uses SPSS 20 software. The sample used is 89 respondents. The analysis tool uses Multiple Linear Regression and the research time is 4 months June-September 2021. The results of the study show: 1) Partially organizational culture affects employee loyalty of PT Parako Ekatama Rangkasbitung 2) Partially compensation affects employee loyalty at PT Parako Ekatama Rangkasbitung 3) There is a joint influence of organizational culture and compensation on employee loyalty of PT Parako Ekatama Rangkasbitung . Organizational culture and compensation simultaneously on loyalty by 35.0%. Based on the results of the study also obtained the following findings: 1) organizational culture is the most dominant variable in influencing employee loyalty 2) compensation is a mediating variable for organizational culture variables in influencing employee loyalty.